Improved MRI methods to quantify retinal and choroidal blood flow applied to a model of glaucoma - Jiang, Zhao; Chernoff, Diane; Galenchik-Chan, Andre; Tomorri, David; Honkanen, Robert A.; Duong, Timothy Q.; Muir, Eric R. (Frontiers in Ophthalmology, 2024)
PurposeBlood flow (BF) of the retinal and choroidal vasculatures can be quantitatively imaged using MRI. This study sought to improve methods of data acquisition and analysis for MRI of layer-specific retinal and choroidal BF and then applied this approach to detect reduced ocular BF in a well-established mouse model of glaucoma from both eyes.MethodsQuantitative BF magnetic resonance imaging (MRI) was performed on glaucomatous DBA/2J and normal C57BL/6J mice. Arterial spin labeling MRI was applied to image retinal and choroidal BF using custom-made dual eye coils that could image both eyes during the same scan. Statistics using data from a single eye or two eyes were compared. BF values were calculated using two approaches. The BF rate per quantity of tissue was calculated as commonly done, and the peak BF values of the retinal and choroidal vasculatures were taken. Additionally, the BF rate per retinal surface area was calculated using a new analysis approach to attempt to reduce partial volume and variability by integrating BF over the retinal and choroidal depths.ResultsOcular BF of both eyes could be imaged using the dual coil setup without effecting scan time. Intraocular pressure was significantly elevated in DBA/2J mice compared to C57BL/6J mice (P<0.01). Both retinal and choroidal BF were significantly decreased in DBA/2J mice in comparison to the age-matched normal C57BL/6J mice across all measurements (P < 0.01). From simulations, the values from the integrated BF analysis method had less partial volume effect, and from in vivo scans, this analysis approach also improved power.ConclusionThe dual eye coil setup allows bilateral eye data acquisition, increasing the amount of data acquired without increasing acquisition times in vivo. The reduced ocular BF found using the improved acquisition and analysis approaches replicated the results of previous studies on DBA/2J mice. The ocular hypertensive stress-induced BF reduction found within these mice may represent changes associated with glaucomatous progression.